Helicobacter pylori attenuates proliferation of RAW264.7 monocytic macrophage cells by downregulating cell cycle genes / Grace Tan Min Yi - Grace , Tan Min Yi (2016)
Helicobacter pylori is a Gram-negative, microaerophilic bacteria that colonizes the gastric epithelium in nearly half of the human population. It is well-established as an etiological agent for gastritis, peptic ulcer and gastric cancer. H. pylori infection begins with the invasion gastric epithelial layer. Subsequent damage of the epithelial layer enables H. pylori penetration into the lamina propria where it encounters macrophages. At present, the effect of low-MOI H. pylori infection on macrophage has not been fully elucidated. In this study, genome-wide transcription regulation of H. pylori-infected RAW264.7 murine monocytic macrophage cells was investigated at MOI 1, 5, 10 and 100. H. pylori-infected RAW264.7 cells displayed enlarged cell size and complexity, and expressed surface activation markers such as F4/80, CD11b, CD83 as well as CD86. Moreover, H. pylori-infected RAW264.7 cells displayed attenuation in cells proliferation through Ki67 cell proliferation assay. However, H. pylori-infected cells (MOI 1, 5, 10) do not displayed cellular apoptotic properties as shown in Annexin V assay. RNA of the non-infected control and H. pylori-infected RAW264.7 cells were subjected for microarray analysis, revealing up and downregulation of 1341 genes and 1591 genes respectively. Quantitative real time-PCR was performed on top 10 upregulated genes and top 10 downregulated genes for results validation. In total, KEGG pathway analysis showed induction in 8 significant pathways while 16 pathways were significantly suppressed. The activation of immune response-related genes in H. pylori-infected RAW264.7 cells, including colony stimulating factors (Csf1, Csf2, and Csf3), pro-inflammatory cytokines (Il-1α, Il1-β, Tnf and Il-23α) was confirmed by quantitative real time PCR and activated surface markers (CD40, CD44, CD200) was confirmed by flow cytometry analysis respectively. Furthermore, KEGG pathway analysis also showed repression of expression in multiple genes encoding for DNA replication and cell cycle. Interestingly, the list of top 10 downregulated genes also comprised Aurora-B kinase (Aurkb), an essential cell cycle regulator responsible in augmenting phosphorylation and activation of cell cycle molecules. Along with this, cell cycle analysis showed that H. pylori infection inhibited cell cycle progression at G1-to-S phase as well as G2 to M phase transitions. The expression pattern of the cell cycle-associated genes was further validated using quantitative real time PCR and confirmed their suppression at the transcription level. Furthermore, immunoblot analysis verified the decreased protein expression of Aurkb and downstream phosphorylation of cyclin-dependent kinase 1 (Cdk-1), centromere protein A (Cenp-A) and also cyclin D caused by H. pylori infection. Lastly, H. pylori infection in primary bone marrow-derived macrophages (BMDM) was performed. Similar cell proliferation inhibition was observed, as in the RAW264.7 cell line. In summary, H. pylori disrupts expression of cell cycle-associated genes, thereby impeding proliferation of RAW264.7 cells, and such disruption may be an immuno-evasive strategy utilized by H. pylori.